Challenges of Expanding Employment Opportunities in the Manufacturing Sector in The Prabowo-Gibran Era - Suryadi; Faizal Amir P Nasution (Jurnal Ketenagakerjaan, 2025)
The administration of Prabowo-Gibran will face challenges in expanding employment opportunities in the manufacturing industry sector. The expansion of employment opportunities is influenced by various internal and external factors. This research aims to analyze the development of knowledge related to employment in the manufacturing industry sector and to identify both internal and external factors affecting this expansion. The research methodology employs a qualitative approach with bibliometric analysis to review scientific literature sourced from the Web of Science database, consisting of 499 documents. It measures several variables related to employment expansion in the manufacturing industry. This method is crucial for understanding the development of a specific field of study and identifying variables associated with employment by utilizing the VOSviewer software.